Pemberdayaan Masyarakat dan Pertumbuhan Ekonomi Lokal Melalui Program Pembangunan Berbasis Desa di Desa Lama: Pengabdian - Mila Naeruz; Azhar Apriandi; Fauzi; Faty Rahmarisa; Amrani; M.Sahnan; Aulia Nabila Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aims to strengthen local economic capacity and improve community welfare through village-based development initiatives in Desa Lama, Hamparan Perak District, Deli Serdang Regency. The program focuses on empowering local communities by providing education, training, and mentoring in areas such as small business management, financial literacy, and the utilization of local resources. The method used includes participatory approaches involving community members, local government, and university partners to ensure sustainability and relevance to the village’s socio-economic context. The results show that after the implementation of the program, there was an increase in community participation in economic activities, improved entrepreneurial skills, and the emergence of small-scale business initiatives managed independently by villagers. In addition, the collaboration between academic institutions and the local government strengthened social capital and supported long-term rural economic growth. This activity demonstrates that integrated village-based development can serve as an effective model for improving local economies and community resilience in rural areas.